Successful Emotions How Emotions Drive Cognitive Performance - Lochner, Katharina; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer, 2016)
This book provides first time insight into whether emotions impact performance of an online ability test. This question is gaining in relevance as online assessment is used increasingly in personnel selection and since it has been shown that emotions impact the way humans think. Moreover, the author demonstrates, for the first time, how short film clips can elicit different emotions in an online setting. Furthermore, she gives an overview of the area of online assessment, of models of intelligence and emotion, and of how emotion and cognition interact. Contents Data Quality in Online Assessment Cognition, Emotions, and How They Interact Study of Online Emotion Induction Study of How Cognition and Affect Interact in Online Assessment Motivation, Type of Task, and Situation as Additional Factors Impacting Performance Target Groups Practitioners in the areas of psychological assessment and psychometrics The Author Dr. Katharina Lochner is the Research Director at international cut-e Group. In this position she connects science and practical use of online assessment.
Data Quality in Online Assessment -- Cognition, Emotions, and How They Interact -- Study of Online Emotion Induction -- Study of How Cognition and Affect Interact in Online Assessment -- Motivation, Type of Task, and Situation as Additional Factors Impacting Performance.
Keywords: Psychology; Cognitive psychology; Psychometrics; Positive psychology; Psychology; Cognitive Psychology; Positive Psychology; Psychometrics; Electronic books